1999
DOI: 10.1093/hmg/8.6.1047
|View full text |Cite
|
Sign up to set email alerts
|

Gene shifting: a novel therapy for mitochondrial myopathy

Abstract: Mutations in mitochondrial DNA (mtDNA) are the most frequent causes of mitochondrial myopathy in adults. In the majority of cases mutant and wild-type mtDNAs coexist, a condition referred to as mtDNA heteroplasmy; however, the relative frequency of each species varies widely in different cells and tissues. Nearly complete segregation of mutant and wild-type mtDNAs has been observed in the skeletal muscle of many patients. In such patients mutant mtDNAs pre-dominate in mature myofibers but are rare or undetecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(88 citation statements)
references
References 21 publications
3
82
1
2
Order By: Relevance
“…Interestingly, resistance training may offer a more optimal solution for patients or elderly individuals with mtDNA mutations. The idea comes from the identification that satellite muscle cells harbor no mtDNA mutation load, thus their activation by resistance exercise, which promotes fusion of these cells and their organelles with exercised myofibers, will thereby shift mtDNA toward a healthier genotype, thus improving mitochondrial quality and function (155). One recent study indicated that the mutation load was not significantly altered in mtDNA mutation patients with resistance training (115), but further research is needed in this area, particularly with aging muscle.…”
Section: Mtdna Tfam and Agingmentioning
confidence: 99%
“…Interestingly, resistance training may offer a more optimal solution for patients or elderly individuals with mtDNA mutations. The idea comes from the identification that satellite muscle cells harbor no mtDNA mutation load, thus their activation by resistance exercise, which promotes fusion of these cells and their organelles with exercised myofibers, will thereby shift mtDNA toward a healthier genotype, thus improving mitochondrial quality and function (155). One recent study indicated that the mutation load was not significantly altered in mtDNA mutation patients with resistance training (115), but further research is needed in this area, particularly with aging muscle.…”
Section: Mtdna Tfam and Agingmentioning
confidence: 99%
“…109 Although this approach has been proven advantageous in clinics to some levels, additional studies are required to define the optimal parameters for exercise regime. 110 3. Gene therapy: Researchers are actively working on wide number of approaches to develop effective treatment of mitochondrial disorders.…”
Section: Molecular Genetic Analysismentioning
confidence: 99%
“…Because satellite cells frequently carry a lower rate of mutant or sometimes no mutation at all, this technique may prove useful in reducing the heteroplasmy of a pathogenic mutation by gene shifting. 81 Muscle regeneration can be induced by injections of substances into muscle (bupivacaine) 11,82 or by isometric exercise causing microtraumas. 84 In support of this, in one patient carrying a nonsense mutation in the COX I gene, recurrent myoglobinuria led to a positive selection of COX positive fibers harboring no mutant mtDNA.…”
Section: Inducing Muscle Regenerationmentioning
confidence: 99%
“…Resistance training using either shortening contractions (concentric) leading to muscle hypertrophy or lengthening contractions (eccentric) leading to segmental muscle necrosis has been proven to induce sufficient traumatic injury to stimulate these satellite cells to be incorporated into the new muscle fibers, a process referred to as gene shifting. 81 It is postulated that stimulation of muscle regeneration in this manner may lead to a normal mtDNA genotype in the regenerated fibers. Preliminary studies injecting bupivacaine hydrochloride (0.75%) to induce muscle necrosis showed satellite cell proliferation exclusively responsible for the derivation of new muscle fibers and an improvement in biochemical activity.…”
Section: Resistance Trainingmentioning
confidence: 99%